2012
DOI: 10.4137/cmc.s8602
|View full text |Cite
|
Sign up to set email alerts
|

Balloon Valvuloplasty of Aortic Valve Stenosis in Childhood: Midterm Results in a Children's Hospital, Mansoura University, Egypt

Abstract: Background:Balloon valvuloplasty was established as an alternative to surgery for treatment of aortic valve stenosis in childhood. Acute complications after balloon dilatation including aortic insufficiency or early death were described.Aim of Work:To analyze early outcome and midterm results of balloon aortic valvuloplasty (BAV) in Children’s Hospital, Mansoura University, Egypt.Subjects and Methods:Between April 2005–June 2008, all consecutive patients of age <18 years treated for aortic valve stenosis (AVS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 38 publications
7
3
0
Order By: Relevance
“…Our survival analysis, with a mean follow-up of 11.4 ± 7 years, revealed that 88 % of patients were alive at 20 years of age, with two-thirds of the cohort free from surgery and over half free from any reintervention. These findings are in line with the literature [1,6,9]. Nevertheless, a second intervention (either surgery or BAV-36 % in our series) appeared unavoidable in a third of patients in the long term [7,12,13].…”
Section: Discussionsupporting
confidence: 94%
“…Our survival analysis, with a mean follow-up of 11.4 ± 7 years, revealed that 88 % of patients were alive at 20 years of age, with two-thirds of the cohort free from surgery and over half free from any reintervention. These findings are in line with the literature [1,6,9]. Nevertheless, a second intervention (either surgery or BAV-36 % in our series) appeared unavoidable in a third of patients in the long term [7,12,13].…”
Section: Discussionsupporting
confidence: 94%
“…22,23 We had 100% success in reduction of the Doppler and catheter peak-to-peak gradient across AoV, and this is comparable with the results of many investigators. [21][22][23][24][25][26][27] Our results are comparable with those of Al Marsafawy et al, in Al-Mansoura, Egypt who reported significant reduction of the gradient in all their cases. 26 However, the mortality was higher in their series (10%) compared to ours 2.7%.…”
Section: Discussionsupporting
confidence: 89%
“…[21][22][23][24][25][26][27] Our results are comparable with those of Al Marsafawy et al, in Al-Mansoura, Egypt who reported significant reduction of the gradient in all their cases. 26 However, the mortality was higher in their series (10%) compared to ours 2.7%. Also, similarly, their cases did not need reintervention by ballooning or surgical AoV replacement.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Instantaneous pressure gradient peak and mean were recorded by continuous-wave Doppler tracing in multiple planes, including apical fivechamber, apical three-chamber, right parasternal, subxiphoid long axis, and suprasternal views, and maximum gradients were considered, as shown in Figure 2. The severity of AI was classified as none, trivial, mild, moderate, and severe or graded from 0 to IV [13]. Angiographic parameters were also noted as aortic and LV pressures, AVA size, balloon size, and degree of AI (if any).…”
Section: Figure 1: Chest X-ray Posterior-anterior View Showing Cardiomentioning
confidence: 99%